Mainstreaming renewable energy in the 21st century - Sawin, Janet L. (Worldwatch Institute, 2004)
The last sentence of Mainstreaming Renewable Energy in the 21st Century is..." The key is ambitious, forward looking; consistent government policies that drive demand for renewable energy create a self-reinforcing market and propel renewables into the energy mainstream during the 21st century